The effects of the non-contingent presentation of safety signals on the elimination of safety behaviors: An experimental comparison between individuals with low and high obsessive-compulsive profiles. (June 2018) - Angelakis, Ioannis; Austin, Jennifer L.
Abstract: Background and objectives: Safety behaviors, defined as engagement in avoidance within safe environments, are a key symptom of obsessive-compulsive and related disorders. They may interfere with daily functioning and as such their emission should be reduced. The purpose of the current study is to investigate the effects of the non-contingent presentation of safety signals (cues produced by safety behaviors) on reducing safety behaviors in participants self-reporting low and high OCD profiles. Methods: In total, 32 participants were asked to play a game to gain points and avoid their loss. After having developed avoidance behavior, evidenced by maintaining all of their earned points, they were exposed to safe environments where no point loss was programmed. In Test 1, safety cues (blue bar) were produced contingent on performing safety behaviors. In Test 2, safety cues were presented continuously without any response requirement. Results: Findings demonstrated that high OCD group displayed higher rates of safety behaviors than low OCD group. However, exposure to the non-contingent presentation of safety signals eliminated their emission in both groups. Limitations: Future studies need to evaluate the effects of different non-contingent schedules on the suppression of safety behaviors. Conclusions: These findings contribute to the literature by demonstrating that non-contingent introduction of safety signals eliminated safety behaviors completely, even in high OCD participants, who performed safety behavior at higher rates. Such a treatment protocol may ameliorate exposure therapy in which response prevention constitutes a key element and is generally associated with increased drop-out rates. Highlights: Safety behaviors constitute a key element of obsessive-compulsive disorders. Cues produced by safety behaviors (safety signals) maintain their emission. Effects of non-contingent safety signal exposure was tested in subjects with OCD. Non-contingent exposure to safety signals eliminated safety behaviors.